REGIONAL SPECIALIZATION AND INDUSTRIAL CONCENTRATION IN THAILAND, 1996-2005 - Apisek Pansuwan (Faculty of Geography, Universitas Gadjah Mada, 2009)
This paper provides a descriptive analysis of the changes in the industrial and spatial concentration that occurred in Thailand from 1996 to 2005. Based on the data from the Department of Industrial Work of the Ministry of Industry and using the Hirschman-Herfindahl index of concentration, the geographical concentration of industries in the study regions was measured. The Hirschman-Herfindahl index has the useful property of being decomposable into sources of changes in the concentration. Moreover, location quotient was also used to measure the regional specialization of the manufacturing industries in Thailand. Results of the analysis indicated that from 1996 to 2005, the decrease in the spatial concentration of manufacturing as well as in the regional specialization in manufacturing in Thailand remained stable to a lesser extent. The results have also indicated that most factories continue to be concentrated in Bangkok and its neighboring areas. It can therefore be best argued that in the case of Thailand, the effect of its trade liberalization policy has been more powerful than its industrial decentralization policy.